Research methodology : - Kothari, S. R. (New Age International Limited, Pub., 2004)
The present book provides the basic tenets of methodological research so that researchers may become familiar with the art of using research methods and techniques. The book contains introductory explanations of several quantitative methods enjoying wide use in social sciences. It covers a fairly wide range, related to Research Methodology. The presentations are uniformly economical and cogent. Illustrations given are meaningful and relevant. The book can be taken as a well-organised guide for researchers whose methodological background is not extensive.